Prognostic value of the Ki-67 proliferation index in patients with triple negative breast carcinoma. Preliminary report. / Valor pronóstico del índice de proliferación Ki-67 en pacientes con carcinoma de mama triple negativo. Reporte preliminar. - Fernández, Ángel; Reigosa, Aldo; Saldivia, Felipe; Castillo, Liliana; Castro, Julio (Investigación Clínica, 2020)
Abstract. The Ki-67 index is a biomarker that indicates the proliferation of cancer cells and is considered an effective prognostic factor for breast cancer. However, a standard cut-off point has not yet been established for the Ki-67 index in triple negative breast carcinomas. Therefore, the objective of this retrospective study was to determine an optimal cut-off point to establish it as a more accurate prognostic factor in the triple negative molecular subtype. The immunohistochemical analysis of the Ki-67 index was performed in 98 patients with breast cancer. The survival study using the Kaplan-Meier method was used to analyze the factors related to overall survival. The cut-off points (20 and 25%) were selected from the univariate analysis because they had the highest Hazard ratio to perform the multivariate analysis. With statistical significance (p<0.001), the analysis revealed that in this series the optimal cut-off point of Ki-67 is 25%, with an independent value regarding the clinicopathological variables considered in the study. These data suggest that the optimal cut-off point at 25% is a more effective prognostic factor for triple negative phenotype breast cancer. Due to the importance of these findings, it is recommended to verify the prognostic value of Ki-67 25% in series with a greater number of patients. Resumen. El índice Ki-67 es un biomarcador que indica la proliferación de células cancerosas y se considera un factor pronóstico eficaz para el cáncer de mama. Sin embargo, todavía no se ha establecido un punto de corte estándar para el índice Ki-67 en carcinomas de mama triple negativo. Por lo tanto, el objetivo de este estudio retrospectivo fue determinar un punto de corte óptimo para establecerlo como un factor pronóstico más preciso en el subtipo molecular triple negativo. El análisis inmunohistoquímico del índice Ki-67 se realizó en 98 pacientes con cáncer de mama. Se utilizó el estudio de supervivencia mediante el método de Kaplan-Meier para el análisis de los factores relacionados con la supervivencia global. Los puntos de corte (20 y 25%) fueron seleccionados del análisis univariado por tener el Hazard ratio más alto para realizar el análisis multivariado. Con significancia estadística (p<0,001), el análisis reveló que en esta serie el punto de corte óptimo de Ki-67 es 25%, con valor independiente respecto a las variables clínico-patológicas consideradas en el estudio. Estos datos sugieren que el punto de corte óptimo en 25% es un factor pronóstico más efectivo para el cáncer de mama con fenotipo triple negativo. Por la importancia de estos hallazgos, es recomendable verificar el valor pronóstico de Ki-67 25% en series con un mayor número de pacientes.